Acute Peritoneal Dialysis in a Patient with Severe Uremic Syndrome and Multiple Hemodialysis Access Failure - Made Dyah Vismita Indramila Duarsa; Gede Wira Mahadita; Yenny Kandarini (Case Reports in Nephrology)
A 67-year-old woman was diagnosed with chronic kidney disease stage V, severe uremia syndrome, hyperkalemia, metabolic acidosis, suspected pulmonary oedema, and multiple hemodialysis access failure. The patient is in a condition that requires emergency hemodialysis, but the patient does not have any access to undergo hemodialysis. The patient then underwent acute peritoneal dialysis and received an adequate response. The patient continued continuous ambulatory peritoneal dialysis and responded well.